Effective Strategies in Formulating Educational Objectives to Achieve the Vision and Mission of Institutions at the Madrasah Aliyah Level in the Riau Islands - Zamsiswaya Zamsiswaya; Syawaludin Syawaludin; Nunung Witono; Juni Mahanis (International Forum of Researchers and Lecturers, 2025)
The precise and effective formulation of educational objectives is crucial in realizing the vision and mission of educational institutions, especially at the Madrasah Aliyah level, which plays an important role in shaping students' character and competencies based on Islamic values. However, in practice, a gap still exists between the formulation of educational objectives and the achievement of the institution’s vision and mission, which impacts the quality of learning and educational management. This study aims to identify and analyze effective strategies implemented by Madrasah Aliyah in formulating educational objectives that align with the institution’s vision and mission. The research method used is qualitative descriptive with a case study approach, involving principals, teachers, and curriculum development teams as research subjects. Data were collected through in-depth interviews, participatory observation, and analysis of educational planning documents. The results show that effective strategies include a participatory approach involving all stakeholders, the use of continuous evaluation as a basis for formulating objectives, and the integration of Islamic values that strengthen character education orientation. The alignment between educational objectives and the institution’s vision and mission has also been proven to enhance the effectiveness of learning program implementation and the achievement of both academic and non-academic student accomplishments. In conclusion, strategic and value-oriented formulation of educational objectives is a key factor in achieving the vision and mission of Madrasah Aliyah, thus requiring the strengthening of managerial capacity and a sustainable evaluation system.